Analysis of Contribution and Effectiveness of Local Taxes and Levies on Southeast Sulawesi Revenue - Nurhayati, Nurhayati; Sarita, Buyung; Saleh, Salma (Journal of Business Management and Economic Development, 2024)
The research aims to assess the contribution of local taxes and levies to Southeast Sulawesi Province's original income and evaluate their effectiveness. Utilizing quantitative descriptive research, findings indicate a consistent high contribution of local taxes from 2018 to 2022, ranging between 98.99% to 99.25%. This demonstrates their significant role in surpassing the 90% mark, thus positively impacting the province's Original Income. Conversely, levies exhibit unsatisfactory performance during this period, with contributions declining notably, hitting a low of 0.01% in 2022. In terms of effectiveness, local taxes consistently surpassed the 100% mark from 2018 to 2021, showcasing successful revenue targets attainment. Although a slight dip occurred in 2022 to 95.81%, local taxes remained effective. Conversely, levies demonstrated exceptional effectiveness in 2018 and 2019, exceeding 120%, indicating proficient management and surpassing revenue targets. The reciprocal relationship between the government and the people, as per stakeholder theory, underscores how effective tax management influences the province's welfare. The positive correlation between local taxes, levies, and regional income stems from improved tax collection principles enforced by stakeholders. In conclusion, while local taxes significantly contribute to regional income, effective levy management is crucial. This study underscores the importance of leveraging tax resources for societal welfare, highlighting the need for continuous evaluation and improvement in tax management strategies.